History of the Spanish Pedagogical Renewal Through its Education Centers: 1876-1972 - Pericacho Gómez, Francisco Javier; Novillo, Miguel Ángel; Argita García, Amaya; Sánchez Cabrero, Roberto; Barrientos Fernández, Amelia; Mañoso Pacheco, Lidia (My University, 2024)
Promoted by some of the most critical sectors of the education community, the history of the Spanish pedagogical renewal (19th and 20th centuries) shows all kinds of experiences representing an innovative, committed and transformative way to understand both pedagogical processes and the school. This article shows the final results of the historical analysis of the Spanish pedagogical renewal from the late 19th century (1876) to the last years of Franco¿s dictatorship (1972), through the different primary education schools considered as references, both public and private. Different studies on the Spanish pedagogical renewal have been examined, as well as media from the period and the main education magazines which acted as tools of expression in each historical period. This analysis was completed with data obtained from the revision of education projects, the direct observation of several cases, and consultation with the most relevant stakeholders. In order to create an overview, this article allows for a gradual understanding of the historical development, and of the cultural, political, social and pedagogical nature of the changing processes experimented through those years. Keywords: pedagogical renewal in Spain, school, history of education, alternative school.